2013
DOI: 10.1016/j.colsurfa.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Controlling gold nanoparticle assembly on electron beam-reduced nitrophenyl self-assembled monolayers via electron dose

Abstract: Electron Beam Lithography is a well-established tool suitable for the modification of substrate surface chemistry. It therefore follows that the deposition and self-assembly of nanoparticles on a surface can be directed using this method. This work explores the effect of electron dose on the electron beam lithographic patterning of selfassembled monolayers (SAMs) on gold surfaces. Electron beam irradiation of the sample induces conversion of the SAM terminal functional aromatic nitro (NO 2 ) moieties to aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In other words, after EB irradiation the SAMs underwent selective reduction. It has previously been reported that EB lithography and the irradiation of x-ray can induce the transition of the SAM terminal function aromatic nitro (NO 2 ) moieties to aromatic amino (NH 2 ) moieties [46][47][48][49][50][51][52][53]. Thus, EB irradiation results in a chemically striped patterned substrate consisting of alternating stripes of SAM with an aromatic NO 2 terminal functionality and SAM with aromatic NH 2 terminal functionality, as shown Figure 2.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In other words, after EB irradiation the SAMs underwent selective reduction. It has previously been reported that EB lithography and the irradiation of x-ray can induce the transition of the SAM terminal function aromatic nitro (NO 2 ) moieties to aromatic amino (NH 2 ) moieties [46][47][48][49][50][51][52][53]. Thus, EB irradiation results in a chemically striped patterned substrate consisting of alternating stripes of SAM with an aromatic NO 2 terminal functionality and SAM with aromatic NH 2 terminal functionality, as shown Figure 2.…”
Section: Methodsmentioning
confidence: 95%
“…The gold coated samples were then cleaned in piranha solution (mixture solution of 30% hydrogen peroxide and concentrated sulfuric acid) (Warning: Piranha solution is very reactive and corrosive) for 5 min at room temperature. 6-(4-nitrophenoxy) hexane-1-thiol (NPHT) was prepared as detailed elsewhere [46]. To deposit the SAMs, a 10 mmol solution of NPHT was created in ethanol solvent, and the gold samples submerged in the solution for 48 h. Deposition was terminated using a 15 s rinse in the solvent and the samples were then dried with nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…6-(4-nitrophenoxy) hexane-1-thiol (NPHT) was prepared as detailed elsewhere. 46 To deposit the SAMs a 10mmol solution of NPHT was created in ethanol solvent, and the gold samples submerged in the solution for 48 h. Deposition was terminated using a 15 s rinse in the solvent and the samples were then dried with nitrogen. The rinse and dry was repeated twice to ensure maximum removal of physisorbed multilayers.…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been reported that EB lithography and x-ray irradiation can induce conversion of the SAM terminal function aromatic nitro (NO 2 ) moieties to aromatic amino (NH 2 ) moieties. [46][47][48][49][50][51][52][53] pre-coated with SAM. It is known that the PMMA block preferentially wets on SAMs that contain polar groups.…”
Section: No2inin02 Mn0ailmentioning
confidence: 99%
“…Many methods for patterning surfaces have been developed to prepare large-area monolayer colloidal crystals, such as photolithography [11,12], X-ray lithography [13], electron beam lithography [14,15] and nano-imprint lithography [16]. However, these methods either demand expensive equipment, require a relatively long time for the fabrication, or give a low throughput, which limits their application.…”
Section: Introductionmentioning
confidence: 99%